3D reconstruction based on archival materials: the case of the Genoese castle on the Panea rock (XV century, Crimea) - Denisenko N.D.; Vodolazhskaya L.N.; Akhunov E.O.; Burlin G.A.; Korolev K.A.; Pipa O.V. (Cultural Heritage and Modern Technologies)
The paper is devoted to the study of the prospects of 3D-reconstruction of archaeological monuments landscape on the basis of archival materials. This approach may be relevant for monuments that have not been preserved to date (or are poorly preserved) due to the influence of anthropogenic and natural factors. This is especially relevant for seismic zones and zones of military operations. In some cases (for example, in the case of the Byzantine fortress Gaspra-Isar (XII-XIII centuries, Crimea) - the monuments may have been destroyed during large construction projects. The research is based on the reconstruction of the landscape of the Genoese fortress on the Panea rock (XV century, Crimea) based on the materials of the works of the South Coast detachment of the Department of Ancient and Medieval Archaeology of the Ukrainian SSR Academy of Sciences Institute of Archaeology in 1966-1968. These materials are stored in the Scientific Archive of the Institute of Archaeology of Crimea RAS. The study uses a technique that can provide a very accurate reconstruction of the landscape on the basis of topographic maps and photographic materials. The methodology can be applied to the reconstruction of now lost archaeological monuments.